2023
DOI: 10.1101/2023.01.05.522832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly multiplexed ddPCR-amplicon sequencing reveals strongPlasmodium falciparumpopulation structure and isolated populations amenable to local elimination efforts in Zanzibar

Abstract: Over the past 15 years, Zanzibar has made great strides toward malaria elimination; yet progress has stalled. Parasite genetic data of Plasmodium falciparum may inform strategies for malaria elimination by helping to identify contributory factors to parasite persistence. Here we elucidate fine-scale parasite population structure and infer relatedness and connectivity of infections using an identity-by-descent (IBD) approach. We sequenced 518 P. falciparum samples from 5 districts covering both main islands usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…These barriers may also explain why pfhrp2/3 deletions appear to be disproportionately prevalent in the Horn of Africa (31)(32)(33)(34)(35)(36)(37)(38). The genetic diversity of P. falciparum infections in Gondar and Ziway was markedly lower (mean HE: 0.54) than previously observed in another low transmission area in Zanzibar (mean HE: 0.73), using the same microhaplotype panel (39), suggesting a smaller parasite population size in Gondar. The direct comparison between two elimination sites corroborates the usefulness of malaria genomic surveillance to understand transmission intensities in different sites.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…These barriers may also explain why pfhrp2/3 deletions appear to be disproportionately prevalent in the Horn of Africa (31)(32)(33)(34)(35)(36)(37)(38). The genetic diversity of P. falciparum infections in Gondar and Ziway was markedly lower (mean HE: 0.54) than previously observed in another low transmission area in Zanzibar (mean HE: 0.73), using the same microhaplotype panel (39), suggesting a smaller parasite population size in Gondar. The direct comparison between two elimination sites corroborates the usefulness of malaria genomic surveillance to understand transmission intensities in different sites.…”
Section: Discussionmentioning
confidence: 69%
“…Multiplexed amplification in microdroplets was performed as previously described (39). The final library at a concentration of 1.6pM, including 25% PhiX v3 control spiked in, was sequenced on a NextSeq 500 instrument (Illumina) using 150 bp paired-end sequencing with dual indexing using NextSeq at the University of Notre Dame Genomics and Bioinformatics Core Facility.…”
Section: Dna Extraction and Multiplex Amplicon Deep Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The network of highly related P. falciparum parasites from 6 shehias in North Pemba provides an excellent example of likely recent near clonal transmission, consistent with an outbreak (Figure 4C). A recent study investigating population structure in Zanzibar also found local population microstructure in Pemba (Holzschuh et al, 2023).…”
Section: Discussionmentioning
confidence: 80%
“…The network of highly related P. falciparum parasites from 6 shehias in North Pemba provides an excellent example of likely recent near clonal transmission, consistent with an outbreak (Figure 4C ). A recent study investigating population structure in Zanzibar also found local population microstructure in Pemba (Holzschuh et al, 2023 ). Overall, given the findings of microstructure with significant local sharing of highly related strains, these small clusters still potentially drive much of the malaria transmission that occurs within the archipelago through routine human movement or mosquito travel between locales (Huestis et al, 2019 ).…”
Section: Discussionmentioning
confidence: 89%